THERMOELECTRIC CONVERTER OF LOW-POTENTIAL HEAT ENERGY - ZAKORDONETS, VOLODYMYR; KUZEMKO, NATALIIA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Nature holds vast reserves of low-grade thermal energy, which are currently either underutilized or not used at all. Tapping into even a small fraction of this energy, even with a minor temperature difference between the heat source and cooler, could significantly reduce the fuel and energy deficit and lessen the economy's reliance on fossil fuels.Low-grade energy sources are broadly categorized into two types: natural and anthropogenic. The former includes surface and groundwater, air, solar radiation, and similar sources. The latter encompasses wastewater from various industrial processes, hot air, and hot production waste. Overall, approximately 70% of the world's energy used in production and energy conversion is wasted. Therefore, the utilization and conversion of diffused low-grade thermal energy for reuse are highly relevant. This primarily involves developing new technologies and exploring novel thermodynamic cycles based on renewable energy sources (RES).One promising avenue in energy-saving technologies is a heat engine with a thermoelectric cycle that converts low-grade thermal energy into rotational mechanical energy for a rotor. Its operation is based on the principle of interaction between the current generated by a short-circuited thermoelectric generator and a magnetic field. This magnetic field is created within the machine's rotor by a system of permanent magnets.The paper analyzes the electromagnetic power, electromagnetic torque, rotor speed, and efficiency factor of the thermoelectric converter  for low-potential heat energy (TEC). We optimized these parameters for both maximum electromagnetic power and maximum efficiency modes. The results show that the electromagnetic power increases quadratically with an increase in the temperature difference between the heat and cold sources. The TEC's efficiency ranges from 1-3%. However, this efficiency is typical for all heat engines operating with small temperature differentials, and since secondary heat is utilized, it should not be the sole determining criterion when evaluating the performance of such machines.
Keywords: renewable energy sources; heat engine; thermoelectric converter